Case reportReccurrent neurotrophic ulcerations in a patient with meningomyelocele – case report - Misterska, Małgorzata; Szulczyńska-Gabor, Joanna; Silny, Wojciech; Czarnecka-Operacz, Magdalena; Jankowski, Roman; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Neuropathic causes of ulcerations of the lower limbs are relatively rare. We present a case of a 29-year old woman with spina bifida and inherent myelomeningocele of the lumbo-sacral region of the spinal column, in whom from early childhood non-painful and non-healing erosions and deep ulcerations appeared within the left foot due to small injuries. Multi-annual inefficacious treatment and lack of proper diagnosis precluded the correct causal treatment and led to amputation of the 5th toe of the left foot, osteolytic changes in the metatarsal bones, and finally to a life-threatening condition